Metastasis to gluteal muscle from high grade transitional cell carcinoma of bladder. Report of a case and review of literature - SPINELLI, M.; GILLIBRAND, R. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
High grade bladder malignancies have tendency to local and distant invasion. The most commonly involved sites are lymph nodes, lungs, bone and liver. Muscle metastases are generally rare and have been described in few cases of Genito-Urinary cancer. In this work we describe a rare case of high grade transitional cell carcinoma from bladder metastatising to the left gluteal muscle together with the review of the pertinent literature.